2009
DOI: 10.1111/j.1365-2109.2008.02112.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of enzyme-linked immunosorbent assay for measurement of faecal cortisol in fish

Abstract: Quanti¢cation of glucocorticoid (GC) levels in faeces has become an established method for the non-invasive assessment of adrenocortical activity. These hormones are frequently determined in plasma samples as parameters of adrenal activity and response to stress. Because GCs are metabolized and excreted with both intact hormone and their metabolites present in faeces, the concentration of GCs can be measured in excreta. Faecal samples present the advantages of easy collection, no stress to the animal and elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…In the previous study stress hormones in mammals and birds were assessed by FCM tests [19]. Fecal corticoid studies on free-living parrotfish and common carp demonstrated that FCM in fecal casts correlated strongly to plasma cortisol level [6,26,27]. Our results demonstrates that it is possible to use FCM analysis as a non-invasive tool to assess stress levels in farmed salmon.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 85%
See 1 more Smart Citation
“…In the previous study stress hormones in mammals and birds were assessed by FCM tests [19]. Fecal corticoid studies on free-living parrotfish and common carp demonstrated that FCM in fecal casts correlated strongly to plasma cortisol level [6,26,27]. Our results demonstrates that it is possible to use FCM analysis as a non-invasive tool to assess stress levels in farmed salmon.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 85%
“…It is crucial to assess corticosteroids in alternative less handling-sensitive and non-invasive biological matrices. These include faecal casts, which have been validated in parrotfish [3,6]. Farmers can perform such sampling themselves, for instance during the weekly sea lice counting.…”
Section: Introductionmentioning
confidence: 99%
“…regulation of metabolism, growth, and development, as well as responses to stress influencing the physiology and endocrinology of the reproductive and immune systems (Moberg 1991; Dobson & Smith 2000; Sjaastad et al 2003; von Borell et al 2007; Schmidt & Soma 2008). Cortisol (and corticosterone, another GC) have been used for assessing physical and psychological stress in a wide range of animals, in matrices such as blood, bird eggs, faeces, saliva, whale blow, urine, feathers, liver and gonad tissue, and more recently hair (Koren et al 2002; Constable et al 2006; Van der Staay et al 2007; Bortolotti et al 2008; Flores-Valverde& Hill 2008; Saco et al 2008; Hogg et al 2009; Lupica & Turner 2009; Okuliarová et al 2010). Faeces, egg, and especially feather and hair samples, have the advantage that they express chronic stress rather than short-term hormonal fluctuations caused by for example circadian rhythms or the stress of hunting (Koren et al 2002; Davenport et al 2006; Bortolotti et al 2008; Saco et al 2008; Okuliarová et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Stress in animals has been measured as catecholamine or corticosteroid hormone concentration in matrices such a blood, feces, urine, feathers, eggs and saliva (Larter & Nagy 2001; Van der Staay et al 2007; Bortolotti et al 2008; Downing & Bryden 2008; Saco et al 2008; Lupica & Turner 2009; Okuliarová et al 2010; Saeb et al 2010). More recently, analyses of hair (Koren et al 2002; Davenport et al 2006; Dettmer et al 2009; Gow et al 2010), and liver and gonad tissue (Flores-Valverde & Hill 2008) have also been included.…”
Section: Introductionmentioning
confidence: 99%